Fine‐grained sediment deposition alters the response of plant CSR strategies on the gravel bars of a highly regulated river. Issue 3 (22nd April 2020) - Janssen, Philippe; Piégay, Hervé; Evette, André
Abstract: Aims: In riverine ecosystems, variations in disturbance and stress intensities along the flood gradient shape vegetation community structure. However, human modifications to the flood regime may change the magnitude of disturbance and stress, leading to different species distribution patterns along environmental gradients. We aimed to study the effects of local‐ and broad‐scale environmental gradients on riparian plant CSR (Competitors–Stress tolerators–Ruderals) strategies along a highly regulated river. Location: Rhône River, France. Methods: We assessed how changes in elevation, fine sediment and temperature influenced CSR strategies of riparian plant communities, by studying variations in the community‐weighted means and the functional dispersion of the CSR values, on gravel bars along a 250 km north–south river corridor. Results: Species with contrasting ecological strategies co‐occurred less on gravel bars subject to fine sediment deposition, leading to patterns of biotic homogenization along the flood gradients. Furthermore, a shift in CSR strategies from ruderal to stress‐tolerant communities occurred along the elevation gradient on bars with low proportions of fine sediments and from stress‐tolerant to ruderal communities along the elevation gradient on bars with high proportions of fine sediments. Regarding the climatic gradient, the mean value of ruderals increased with temperatures. Also, for stress tolerators, the dispersion value diverged between the northern and southern gravel bars when the proportion of fine sediments was low and converged when the proportion of fine sediments was high. Conclusions: Overbank fine sedimentation alleviates the intensity of stress along not only the elevation gradient but also the climatic gradient. By homogenizing the functional composition of communities, this process may have detrimental consequences for riparian plant diversity, especially of ruderal plants in the littoral zone. In regulated river systems, restoration measures should therefore promote an increase in the intensity of: (a) disturbance through the reactivation of bedload supply and transport; and (b) stress through increased flow dynamics. Abstract : Deposition of fine sediments induces changes in the response of stress‐tolerant and ruderal communities to the flood gradient and a decrease in the co‐occurrence of species with contrasting ecological strategies on gravel bars. This leads to biotic homogenization along environmental gradients, with potentially detrimental consequences for riparian biodiversity and its conservation, especially for ruderal pioneer communities in the littoral zone.